Intra‐couple discordance in preconception syphilis screening for both spouses: a national and population‐based survey in China, 2013–2018. (6th October 2021) - Zhou, Q; Yang, Y; Wang, L; Chen, X; Xu, Q; Wang, Q; Shen, H; Xu, Z; Zhang, Y; Yan, D; Peng, Z; He, Y; et al.
Abstract : Objective: The antenatal screening strategy remains inadequate for eliminating congenital syphilis. To further eliminate maternal fetal transmission, preconception syphilis screening is considered an option. In this study, we investigated syphilis seropositivity and intra‐couple discordance among married couples planning a pregnancy in China to provide essential baseline evidence for preconception syphilis screening. Design: Population‐based survey. Setting: National preconception registered data. Population: Married Chinese couples planning conception within 6 months between 2013 and 2018. Methods: Syphilis was screened using rapid plasma reagin (RPR); infection self‐reporting and sociodemographic characteristics were collected through questionnaires and medical records, respectively. r 3.2.2 and arcgis 10.2 were used for statistical analyses and geographic mapping. Main outcome measures: RPR seropositivity. Results: Among 31 955 041 couples, 29 737 172 (93.06%) had complete RPR results for both spouses; of those, 0.62% (186 100) were seropositive, with dramatic intra‐couple discordance, with 0.33% positivity in wives, 0.24% positivity in husbands and 0.05% positivity in both spouses. Across time, both seropositivity and intra‐couple discordance remained stable. Seropositivity in different regions varied significantly, with provincial rates ranging geographically from Tibet (0.8%) to Hebei (0.2%) ( P < 0.05). Economic level was an independent factor for this regional variation, with seropositivity increasing as gross domestic product income decreased ( P < 0.05). Conclusions: Intra‐couple discordance in seropositivity for syphilis is notable among couples, with a considerable rate of pre‐existing syphilis before pregnancy. Thus, screening both spouses during integrated preconception health care is recommended for further eliminating maternal–fetal transmission. Tweetable abstract: Intra‐couple discordance in seropositivity for syphilis is notable among couples, with a considerable rate of pre‐existing syphilis before pregnancy. Screening both spouses during integrated preconception health care is recommended to further eliminate maternal–fetal transmission. Tweetable abstract: Intra‐couple discordance in seropositivity for syphilis is notable among couples, with a considerable rate of pre‐existing syphilis before pregnancy. Screening both spouses during integrated preconception health care is recommended to further eliminate maternal‐fetal transmission.